Evaluation Research of the Project on Long-term Care System for Elderly Persons, Baan-Lum Sub- District, Wihan-Dang District, Saraburi Province - Sirisomboon, Rawewan; Chunthawong, Napattarakrit (Journal of Health Science of Thailand, 2017)
The objective of this study was to explore improvement factors for a project on long-term care system for elderly persons. The project iam was to support a community to take care of dependent elderly persons to become healthy and not living alone. The Stake’s Evaluation Model and Stufflebeam’s CIPP Model were applied in the study which was conducted during January - June 2015. The samples were comprised of 2 groups: (1) the administrative group and related committee members and (2) care givers. Data were collected by using questionnaire, group interviews and in-depth interviews; and were analyzed by using mean and standard deviation for quantitative data and content analysis for qualitative ones. It was found that both sample groups were highly satisfied with the project in all 4 aspects which included (1) contexts, (2) inputs, (3) processes and (4) results. The project was in line with the current situation and could be supported to meet the expectations. The suggestions to improve the project included (1) provision of sufficient and continuous funding, (2) sufficient number of care managers to justify the workload, (3) capacity building of the working group, (4) increasing workers’ morale, (5) proper selection of care givers to ensure high commitment in caring the elderly. Suggestions to improve the process were (1) sufficient and continuous provision of wage for care givers, (2) development of a communication channel to coordinate among working persons, (3) provision of budget to procure necessary equipment for elderly person and dependent persons, (4) review the contents and method of training using problems of local elderly persons as example, and provision of practical working manual to support care givers, and (5) adjustment of training time to allow trainees to conveniently allocate their time from their routine activities.